Seedless synthetic branched gold nanoshells for chemo-thermal antitumor therapy. Issue 23 (19th May 2020) - Li, Lei; Fu, Yihan; Xu, Zichuang; Zhang, Xuwu; Hao, Zining; He, Yaqian; Gao, Wenbin; Gao, Dawei
Abstract : The production of BGNS was demonstrated. Abstract : Gold nanomaterials (GNMs) are used in photothermal therapy due to their superior optical properties and excellent biocompatibility. However, the complex preparation process involving seed-mediated growth limits further clinical applications of GNMs. Herein, a novel one-pot approach to rapidly prepare liposome-based branched gold nanoshells (BGNS) as an antitumor drug nanocarrier is reported. This efficient seedless synthesis realized tunable absorption peaks of BGNS through controlling the concentration of the Au precursor solution, obtaining high absorbance in the near-infrared (NIR) window to achieve a superior photothermal effect. Hyperthermia during NIR laser irradiation can ablate the tumor and trigger drug release to achieve combined treatment. After laser irradiation, the nanocarriers disintegrated into individual gold nanoparticles (size: about 8 nm), which can be metabolized by the kidneys. Cell experiments in vitro and experiments involving mice with tumors have confirmed that the nanodrugs have strong antitumor effects. Such a flexible method provides a universal approach for rapidly preparing liposome-based gold nanoshells, which have the potential for large-scale preparation for further clinical applications.